Role of allelopathic potential of Crotalaria spp. L. to control Panicum maximum Jacq. weed - Holanda, I. R. [UNESP]; Martins, H. L. [UNESP]; Mata, J. F.; Korasaki, V.; Nepomuceno, M. P. [UNESP]; Alves, P. L.C.A. [UNESP] (International Allelopathy Foundation, 2024)
This study aimed to evaluate the allelopathic potential of Crotalaria spp. to control guinea grass (Panicum maximum Jacq.). Experiments were done on germination and development of P. maximum in Petri-plate Lab Bioassays with the seed exudates of germinating seeds germination water of seed and leaf extract of C. juncea and also in Pot Culture coexistence by sowing and transplantation of two test species. Among the species studied, C. juncea gave the best result to inhibit the germination of target plant, hence, it was selected for further studies. The germination results showed that the highest densities (5, 10 and 20) of C. juncea affect different stages of P. maximum. The higher the concentration of bioextract from C. juncea, the lower was development of P. maximum was decreased with doses from 25 to 100 % for its control. The greater was the density and concentration of C. juncea extracts, the greater was the decrease in germination speed, germination (%), root length, plant height and dry mass weight of P. maximum.
Keywords: Allelopathic potential; Crotalaria juncea; germination; guinea grass; herbicide; Panicum maximum; Phytochemical; seedling growth; weeds